Investigation of the intra and inter-day reliability of the athletic shoulder test using the wii balance board in volleyball players - Çiftçi, M. C.; Çelik, S.; Çabuk, S.; Ulupinar, S.; Ince, I. (BMC Sports Science, Medicine and Rehabilitation, 2025)
This study investigates the intra-day and inter-day reliability of the athletic shoulder test (AST) using the Nintendo Wii Balance Board (NWBB) in volleyball players. Twenty experienced players aged 14.48 ± 1.327 years participated, with no chronic health issues or injuries. Using a prospective cohort design, participants performed two trials in each of the I, Y, and T positions with both arms across three sessions conducted on two separate days. Reliability was assessed using standard error of measurement (SEM), minimum detectable change (MDC), and coefficient of variation (CV). Intra-day ICC values ranged from 0.908 to 0.969, and inter-day ICC values ranged from 0.819 to 0.948. SEM values varied from 1.996 to 6.781 N, while MDC values ranged from 5.533 to 18.708 N. CV values were within acceptable limits. These results indicate that the AST using NWBB provides good to excellent reliability for both intra-day and inter-day measurements in volleyball players.